2022
DOI: 10.1155/2022/2580004
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between Pain Scores and Disc Height Changes after Discectomy in Patients with Lumbar Disc Herniation: A Systematic Review and Meta-Analysis

Abstract: Background. Surgery can reduce and improve lumbar disc herniation, but some patients still have pain after surgery, and the relationship between lumbar disc height and pain after surgery is still unclear. Objective. The main objective is to investigate the relationship between lumbar disc height and postoperative pain. Methods. We searched Pubmed, Web of Science, the Cochrane library, and Embase online for cohort studies or RCT studies on discectomy and assessed the quality of the included articles using the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Although the results of this study were stable, preoperative inflammatory factors were not considered, and the sample size was small and remains to be studied in depth. Also postoperative psychotic symptoms could be related to many other factors like perioperative pain, which deserves further exploration too [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of this study were stable, preoperative inflammatory factors were not considered, and the sample size was small and remains to be studied in depth. Also postoperative psychotic symptoms could be related to many other factors like perioperative pain, which deserves further exploration too [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al recently demonstrated that the degree of back pain after surgery showed a positive correlation with disc space height. 33 In our cohort, both anterior and posterior disc space height showed significant increases (P < 0.001) at every follow-up time point. Likewise, multiple studies have linked a decreased PI-LL mismatch value to improved outcomes.…”
Section: Discussionmentioning
confidence: 53%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%